2005
DOI: 10.1080/00016480510026890
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons between Neural Response Imaging thresholds, electrically evoked auditory reflex thresholds and most comfortable loudness levels in CII Bionic Ear users with HiResolution™ sound processing strategies

Abstract: For 8 patients (53 stimulating electrodes) the correlation between tNRI threshold and M level was r=0.675 (p=0.000) and that between first NRI thresholds and M level was r=0.741 (p=0.000). On average the M-level value was 20 CU (Current Unit) lower than the first NRI threshold value and 12 CU higher than the tNRI threshold value. The M-level patterns across the electrode array overall were similar to the tNRI or first NRI threshold patterns. For 7 patients (112 stimulating electrodes) the correlation between E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 4 publications
2
34
0
Order By: Relevance
“…Electrically evoked electrophysiological measures to single pulses tend to occur at higher levels than behavioral thresholds to pulse trains, falling closer to the most comfortably loud level (Gordon et al, 2004). Indeed, responses from the auditory nerve and brainstem can be as much as 40 current units above behavioral measures Gordon et al, 2004;Han et al, 2005;Cafarelli Dees et al, 2005) and alone do not provide sufficiently accurate predictions of behavioral thresholds to use in individual implant users Brown et al, 1999Brown et al, , 2000Gordon et al, 2004).…”
Section: Electrophysiological and Behavioral Thresholdsmentioning
confidence: 95%
“…Electrically evoked electrophysiological measures to single pulses tend to occur at higher levels than behavioral thresholds to pulse trains, falling closer to the most comfortably loud level (Gordon et al, 2004). Indeed, responses from the auditory nerve and brainstem can be as much as 40 current units above behavioral measures Gordon et al, 2004;Han et al, 2005;Cafarelli Dees et al, 2005) and alone do not provide sufficiently accurate predictions of behavioral thresholds to use in individual implant users Brown et al, 1999Brown et al, , 2000Gordon et al, 2004).…”
Section: Electrophysiological and Behavioral Thresholdsmentioning
confidence: 95%
“…Investigators have also assessed the efficacy of ESRT in predicting comfort levels for optimal programming and they found ESRT to be of greater predictive value than ECAP for estimation of behavioral comfort levels [8,10,11]. Postoperative ESRT thresholds show high correlations with behaviorally obtained comfort levels and help predict the maximum comfort level pattern across electrodes [8].…”
Section: Discussionmentioning
confidence: 99%
“…In the past, correction factors proposed to predict threshold and comfort levels from objective measures, were based on the difference between objective thresholds and at least one behavioral measure (Abbas et al [6], Zimmerling and Hochmair [15], Brown and Carolyn [7]). Subsequent literature suggests that correction factors based on ECAP, ESRT and EABR thresholds are needed to predict behavioral levels required for programming in difficult situations (Di Nardo et al [13], Han et al [10], Caner et al [11]). These studies suggested extrapolation of the averaged value calculated by these correction factors, across the array in order to set behavioral levels.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations